Review: Peran Enzim dalam Meningkatkan Kualitas Kopi - Dany Ardiansyah; Helen Tjota; Warsono El Kiyat (JURNAL AGRI-TEK : Jurnal Penelitian Ilmu-Ilmu Eksakta, 2018)
Indonesia is the third largest coffee producing nation in the world after Brazil and Vietnam. The types and the characteristics of Indonesian coffee are different in each area but the main important factor of consumer acceptance depends on its bitterness level. Chlorogenic acid lactone is a compounds that play an important role as contributor to the coffee bitterness that are formed during the roasting process of coffee bean because of its precursor chlorogenic acid. Chlorogenic acid is commonly found in many plants. One of them can be found in coffee with high concentration. Chlorogenic acid lactone (bitter compound) can be hydrolyzed to chlorogenic acid (non-bitter compound) using hog liver esterase and chlorogenate esterase.Â  This study aimed to analyze the use of these enzymes to decrease the level of bitterness in coffee. The results indicated that HLE and chlorogenate esterase effectively hydrolyzed chlorogenic acid lactones in coffee.Â  Based on the sensory test, coffee extracts treated with enzymes were less bitter than the untreated coffee extracts. If it was associated with Indonesian local coffee then the method can be done with chlorogenate esterase that was in accordance with the legal guarantee of halal product.